PERANCANGAN INTERIOR MOESLIM CULTURE ARTSPACE DI KOTA DENPASAR - Cindy Paramitha Sugianto; A.A Gde Tugus Hadi Iswara; I Kadek Pranajaya (Jurnal PATRA, 2020)
Islamophobia is a disease of excessive fear of Islam, due to excessivetrauma, such as the impact of the Bali I bombing and Bali II bombingcarried out by terrorists who use the name Islam. Islamophobia in Bali hasnot been resolved properly, due to the lack of approach between Muslimand non-Muslim communities in Bali regarding Muslim culture and theunavailability of commercial buildings based on cultural heritage regardingIslamic culture. Therefore, we need a place or facility that canaccommodate the needs of the Muslim community who want to take anapproach such as an artspace that raises the history of the early entry ofIslam in Bali, the development of Islamic culture in Bali after theoccurrence of alkuturation, and provides new insights that were notpreviously known by the community. non-Muslims. Where in this paperwill focus on interior design artspace in the city of Denpasar, entitledDesigning the Moeslim Culture Artspace in Denpasar City. keywords: artspace, culture, design, moeslim Islamophobia merupakan sebuah penyakit ketakutan berlebih terhadap islam, akibat trauma yang berlebih, seperti dampak dari bom bali i dan bombali ii yang dilakukan oleh teroris yang mengatas namakan islam.Islamophobia di bali belum dapat teratasi dengan baik, karena minimnyapendekatan antara masyarakat muslim dan non-muslim di bali mengenaikebudayaan umat muslim serta, belum tersedianya bangunan komersilyang berbasis cagar budaya mengenai kebudayaan islam. Oleh karena itudiperlukan sebuah tempat atau fasilitas yang dapat mewadahi kebutuhanmasyarakat muslim yang ingin melakukan suatu pendekatan seperti artspace yang mengangkat sejarah awal masuknya islam di bali, perkembangan kebudayaan islam di bali setelah terjadinya alkuturasi, sertamemberikan wawasan baru yang sebelumnya belum di ketahui olehmasyarakat non-muslim. Dimana dalam penulisan ini akan berfokus pada perancangan interior ruang karya di kota denpasar, yang berjudulPerancangan Pusat Seni Kebudayaan Islam Di Kota Denpasar. kata kunci : kebudayaan, muslim, perancangan, pusat seni.